Kultura słowa mówionego jako element życia codziennego na ziemiach polskich w dobie baroku - Laddach, Agnieszka (Acta Universitatis Lodziensis. Folia Historica, 2014)
The article presents the forms of occurrence of the words spoken in everyday life in the Baroque period. It analyzes the Baroque thought of rhetoric, post-Tridentine way of proclaiming the Word of God, speech in the service of politics. In the next part the article refers to the word as a communication tool and a means of experiencing everyday life. The last section presents the function of migrants, who have included knowledge of the world in his short stories. All posts represent the activity of speakers in the Polish Kingdom. End presents a brief synthesis of the culture of the spoken word in the context of analyzed space-time.